Pengembangan Aplikasi Buku 16 Administrasi Koperasi Berbasis Website Di Dinas Koperasi Dan UMKM Kota Padang - Annisa Eka Sari; Menik Kurnia Siwi (Jurnal Salingka Nagari, 2022)
This research aims is to determine and analyze the use of the “Aplikasi Buku 16 Administrasi Koperasi” at the Padang City Cooperative and MSME Service (Admin Studies on several Cooperatives in Padang City). This type of research is research and development (R&D). The subject of this research is cooperative admins through small-scale trials. research approach using qualitative methods. With the collection of data taken by the method of interviews, observation, documentation, and questionnaires .The results of this study show that (1) the application is suitable for use in cooperative activities, (2) the application is well received by the research admin, and (3) the application still has shortcomings that must be corrected so that it can be used in all cooperatives in the city of Padang.